Stages of PPP and Principal–Agent Conflicts: The Swedish Water and Sewerage Sector. Issue 1 (2nd January 2018) - Smith, Elin; Umans, Timurs; Thomasson, Anna
ABSTRACT: The focus of this article is on public–private partnerships (PPPs). The aim is to both theoretically and empirically illustrate PPP agency problems in four PPP stages, as well as to identify potentially relevant solutions to the agency problems. The study employed a longitudinal case study of one PPP in a municipality in southern Sweden. Through an analysis based on interviews, observations, and documents, the study illustrates a number of agency problems faced by PPPs and highlights the importance of resource allocation, stakeholder management, and the creation of a common identity in reducing these problems.